The legal mechanism of customs clearance of the goods movement. - М. Г. Шульга (Теорія і практика правознавства, 2016)
The article is devoted to the disclosing of essence the customs clearance of goods while moving across the customs border of Ukraine. The author concentrates on the formation of the legal mechanism of customs clearance, starting with the first of the Customs Code of Ukraine